Dynamics of Atmospheres and Oceans - Dynamics of Atmospheres and Oceans (Elsevier, 2026)
Dynamics of Atmospheres and Oceans is an international journal for research related to the dynamical and physical processes governing atmospheres, oceans and climate. Authors are invited to submit articles, short contributions or scholarly reviews in the following areas: Dynamic meteorology; Physical oceanography; Geophysical fluid dynamics; Climate variability and climate change; Atmosphere-ocean-biosphere-cryosphere interactions; Prediction and predictability; Scale interactions. Papers of theoretical, computational, experimental and observational investigations are invited, particularly those that explore the fundamental nature - or bring together the interdisciplinary and multidisciplinary aspects - of dynamical and physical processes at all scales. Papers that explore air-sea interactions and the coupling between atmospheres, oceans, and other components of the climate system are particularly welcome.
FI 0.49
Q2
Keywords: Earth; Space & Environmental Sciences; Oceanography; Acuerdos transformativos; Transformative agreements; Dinámica atmosférica; Oceanografía física; Interacción atmósfera-océano; Climatología; Circulación atmosférica; Procesos dinámicos